DAMPAK BROKEN HOME PADA ANAK MUDA DAN SOLUSINYA - Juwinner Dedy Kasingku; Alan Hubert Sanger; Dinny Anggreiny Geotrida Gumolung (KOLONI, 2022)
This article aims to find a good solution for children whose families are not doing well, which can affect their social life, which is what is known as a "broken home." There are so many broken-home children who are in bad company or can't be controlled by their parents. And many people still think that children from broken homes are naughty and cannot be managed, so in the end, they will only become community trash. There are so many broken-home children who use this excuse to seek bad associations. Therefore, it is necessary to encourage and motivate both parents so that children do not experience this because of separation from their parents. This article was carried out using data collection techniques, namely related journals, and articles. The findings of this article take the form of encouragement and motivation that each father and mother provide in carrying out their roles as parents. Keywords: broken-home, children, parents